2022
DOI: 10.3390/nano12142382
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelation of Synthesis Conditions and Wettability Properties of the Porous Anodic Alumina Membranes

Abstract: The results of studies on the wettability properties and preparation of porous anodic alumina (PAA) membranes with a 3.3 ± 0.2 μm thickness and a variety of pore sizes are presented in this article. The wettability feature results, as well as the fabrication processing characteristics and morphology, are presented. The microstructure effect of these surfaces on wettability properties is analyzed in comparison to outer PAA surfaces. The interfacial contact angle was measured for amorphous PAA membranes as-fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 74 publications
(90 reference statements)
0
6
0
2
Order By: Relevance
“…The technique illustrated by Dudarev et al 73 deal with the electronic correlation effect on Ce-f, Mn, Cu and V-d orbital's. According to the literature, 26,74,75 the effective U value chosen to be 4 eV per Ce, 4 eV per Mn, 5 eV per Cu and 2 eV per V respectively and the exact exchange a for Ce is 0.35 eV is used throughout the calculation. The interstitial region is extended on a plane wave basis with K max = 6/R MT as the cut-off value, the wave function is ubiquitous in the spherical harmonics contained within the muffin-tin spheres, which together make up the unit cell of the FPLAPW technique.…”
Section: Computational Detailmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique illustrated by Dudarev et al 73 deal with the electronic correlation effect on Ce-f, Mn, Cu and V-d orbital's. According to the literature, 26,74,75 the effective U value chosen to be 4 eV per Ce, 4 eV per Mn, 5 eV per Cu and 2 eV per V respectively and the exact exchange a for Ce is 0.35 eV is used throughout the calculation. The interstitial region is extended on a plane wave basis with K max = 6/R MT as the cut-off value, the wave function is ubiquitous in the spherical harmonics contained within the muffin-tin spheres, which together make up the unit cell of the FPLAPW technique.…”
Section: Computational Detailmentioning
confidence: 99%
“…The technique illustrated by Dudarev et al 73 deal with the electronic correlation effect on Ce-f, Mn, Cu and V-d orbital's. According to the literature, 26,74,75 the effective U value chosen to be 4 eV per Ce, 4 eV per Mn, 5 eV per Cu and 2 eV per V respectively and the exact exchange α for Ce is 0.35 eV is used throughout the calculation.…”
Section: Computational Detailmentioning
confidence: 99%
“…Nanowires and nanotubes are promising materials for futuristic devices due to their exceptional electronic, magnetic, optoelectronic, and mechanical properties . The nanowires impregnated inside porous templates have potential applications such as magnetic storage materials, charge storage nanocapacitors, optoelectronic devices, magnetic sensors, high-frequency switches, logic devices, microwave devices, spin waveguides, spin pumping aides, high hardness coating materials for tribological applications, and so forth. Muthukumar et al observed friction and wear behavior of nanocomposite coatings where copper nanorods are impregnated in ordered nanoporous alumina (NPA). Improved wear resistance is observed for NPA with copper phase compared to NPA during dry reciprocating friction test.…”
Section: Introductionmentioning
confidence: 99%
“…Yue Qi et al use copper (Cu) foam as a template reducing ions etching and shielding the electrical field to synthesize flat graphene on a glass substrate by plasma-enhanced chemical vapor deposition [ 16 ]. D. I. Tishkevich et al demonstrated template-assisted method is an efficient way to improve the wettability property of aluminum and can protect deposited Ti/Al 2 O 3 /Ni composite material avoiding corrosion [ 17 , 18 ]. Controllable gas flow and etching are two efficient ways to realize high crystallinity VFLG synthesis.…”
Section: Introductionmentioning
confidence: 99%